The Power of Language in Indonesia’s Reformation - Muchariman, Randi (Political Science Program, Universitas Negeri Semarang, 2019)
Indonesia’s Reformation in 1998 is a political change driven by the power of civil society and very much determined by the discourse in hegemonic struggle. One of the most influential intellectual ideas and leadership styles of reformation and civil society is suggested by Nurcholish Madjid. This article examines the twenty-year problems of Reformation in the view of Gramsci’s theory of hegemony by analyzing Nurcholish Madjid’s ideas. There is an intellectual imperialism which makes the national ideas embedded in the Preamble of the 1945 Constitution unable to be developed to guide the national life due to the irrelevant social sciences. This article uses the approach of discourse analysis on Indonesian Preamble of the 1945 Constitution text. The explanation shows the possibilities and the expectations after twenty years of Reformation in Indonesia.